The family business map: Framework, selective survey, and evidence from Chinese family firm succession - Bennedsen, Morten; Fan, Joseph P.H.; Jian, Ming; Yeh, Yin-Hua (Journal of Corporate Finance, 2015)
This paper analyzes the causes and consequences of founding family engagement in firm ownership and management. We hypothesize that families manage their firms because they are able to make contributions that non-family managers cannot provide. However, roadblocks arising from within the family, from markets, and from surrounding institutions challenge family ownership. We propose a new framework for organizing these assets and roadblocks, called the family business map; this framework is useful for categorizing the papers presented in this Special Issue. We support the predictions of the framework with evidence from Chinese family firm succession, and conclude that family firm organization is an adaptation to environmental opportunities and constraints. We end the paper with suggestions for future research.